If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(w + -5) = -18 Reorder the terms: -2(-5 + w) = -18 (-5 * -2 + w * -2) = -18 (10 + -2w) = -18 Solving 10 + -2w = -18 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + -2w = -18 + -10 Combine like terms: 10 + -10 = 0 0 + -2w = -18 + -10 -2w = -18 + -10 Combine like terms: -18 + -10 = -28 -2w = -28 Divide each side by '-2'. w = 14 Simplifying w = 14
| -6n-20=-12n+4(1-3n) | | 10-2px=1000-2(100)+4(10)-2(2)+20(200)-3(20)+6(50)+8(30)+4(40) | | 2s-6=112 | | (V+5)(V+3)= | | 10q-39=9q-29 | | -2=-4/y | | 40=1/2(b+28) | | 2-5d=72 | | 5/6=u-2/9 | | H-2/3=2 | | 5x-1=1/729 | | 56=1/2(75+b) | | p=64d+4032 | | 875=70+55 | | 4(2y+3)-12y= | | 11q-3q-8=16 | | 875=70x+55y | | W^2-6w-14=0 | | -12=-3(z-11) | | 2x^2-4x=200 | | 7-t+14=19 | | 3(g+3)=18 | | 2x+3=4x+12 | | 6(0.3)=6(4(0.3)+1) | | 1/2=12x-30= | | 7.6m-1.8=64.32 | | 13-t=11 | | x^3-36x^2+396x-1296=0 | | 1/2=18x-30 | | 6z+0.36=25.72 | | -18n+4(1+5n)=-6n-14 | | 2c+4=25 |